Powers of the curvature operator of space forms and geodesics of the tangent bundle - Sakharova, E.; Yampolsky, A. (Український математичний журнал, 2004)
It is well known that if Г is a geodesic line of the tangent (sphere) bundle with Sasaki metric of a locally symmetric Riemannian manifold, then all geodesic curvatures of the projected curve λ=π₁₄₆₃₋₀₁ Г are constant. In this paper, we consider the case of the tangent (sphere) bundle over real, complex, and quaternionic space forms and give a unified proof of the following property: All geodesic curvatures of the projected curve are zero beginning with k₃, k₆, and k₁₀ for the real, complex, and quaternionic space forms, respectively. Відомо, що якщо Г — геодезична лінія дотичного (сферичного) розшарування з метрикою Сасакі локально-симетричного ріманона многовиду, то всі геодезичні кривизни спроектованої кривої λ=π₁₄₆₃₋₀₁ є константами. У даній статті розглянуто випадок (сферичного) дотичного розшарування над дійсними, комплексними та кватерніонними просторовими формами і наведено уніфіковане доведения наступної властивості: всі геодезичні кривизни спроектованої кривої дорівнюють нулю, починаючи з k₃, k₆, та k₁₀ відповідно для дійсної, комплексної та кватерпіонної форм.